Evaluation of hydroponic systems for organic lettuce production in controlled environment - Chowdhury, Milon; Samarakoon, Uttara C.; Altland, James E. (Frontiers in Plant Science, 2024)
Organic farming methods, including the use of organic substrates, fertilizers, pesticides, and biological control, are gaining popularity in controlled environment agriculture (CEA) due to economic benefits and environmental sustainability. However, despite several studies focusing on the preparation and evaluation of liquid organic fertilizers, none have explored the compatibility of these fertilizers with different hydroponic systems. Therefore, the objective of this study was to evaluate lettuce production using a liquid organic fertilizer under different hydroponic systems. Four distinct hydroponic methods were selected: nutrient film technique (NFT), deep water culture (DWC) (liquid culture systems), and Dutch bucket (DB), regular plastic container (RPC) (substrate-based systems).'Green Butter' lettuce was grown using a liquid organic fertilizer (Espartan) for four weeks. Shoot growth parameters (e.g., shoot width, number of leaves, leaf area, foliar chlorophyll content, fresh weight, and dry weight) and root growth parameters (e.g., root length, fresh weight, and dry weight) were measured. The growth difference of lettuce under the DB and RPC systems was negligible, but the growth in RPC was 29% to 60% and 15% to 44% higher than the NFT and DWC systems, respectively, for shoot width, number of leaves, leaf area, shoot fresh weight and dry weight. Root parameters were nearly identical for the NFT and DWC systems but significantly lower (21% to 94%) than the substrate-based DB and RPC systems. Although lettuce grown in the NFT system showed the least growth, its mineral content in the leaf tissue was comparable or sometimes higher than that of substrate-based hydroponic systems. In conclusion, the tested liquid organic fertilizer is suitable for substrate-based hydroponic systems; however, further evaluation of different liquid organic fertilizers, and crop species is required.